Human cytomegalovirus microRNAs are carried by virions and dense bodies and are delivered to target cells - Mohammad, Abdul-Aleem (J Gen Virol, 2017)
Human cytomegalovirus (HCMV) infection results in the production of virions, dense bodies (DBs) and non-infectious enveloped particles, all of which incorporate proteins and RNAs that can be transferred to host cells. Here, we investigated whether virions and DBs also carry microRNAs (miRNAs) and assessed their delivery and functionality in cells. Human lung fibroblasts (MRC-5) were infected with the HCMV strain AD169, and conditioned cell culture medium was collected and centrifuged. The pellets were treated with RNase-ONE, and the virions and DBs were purified with a potassium tartrate–glycerol gradient and dialysed. The virions and DBs were incubated with micrococcal nuclease, DNA and RNA were extracted and then analysed with TaqMan PCR assays, while the proteins were examined with Western blots. To assess the delivery of miRNAs to cells and their functionality, virions and DBs were irradiated with UV light. The purity of the virions and DBs was confirmed by typical morphology, the presence of the structural protein pp65 and the HCMV genome, the ability to infect MRC-5 cells and the absence of the host genome. RNA analysis revealed the presence of 14 HCMV-encoded miRNAs (UL22A-5p, US25-1-5p, UL22A-3p, US5-2-3p, UL112-3p, US25-2-3p, US25-2-5p, US33-3p, US5-1, UL36-5p, US4-5p, UL36-3p, UL70-5p and US25-1-3p), HCMV immediate-early mRNA and long non-coding RNA2.7, moreover, two host-encoded miRNAs (hsa-miR-218-5p and hsa-miR-21-5p) and beta-2-microglobulin RNA. UV-irradiated virions and DBs delivered viral miRNAs (US25-1-5p and UL112-3p) to the host cells, and miR-US25-1-5p was functional in a luciferase reporter assay. We conclude that virions and DBs carry miRNAs that are biologically functional and can be delivered to cells, which may affect cellular processes.